Reproductive health risk evaluation in NHLS histopathology laboratories. - Mizan, Gabriel Eduardo (My University, 2014)
Introduction The National Health Laboratory Service (NHLS) is a public health laboratory network consisting of 349 diagnostic pathology laboratories which employ approximately 4200 laboratory personnel. These laboratory workers (the majority of whom are females) may be exposed to various occupational health hazards during the course of their work, including chemical, physical, biological, ergonomic and psychosocial hazards. Some of these hazards may specifically affect the reproductive ability of both male and female workers. Study Objectives The aim of this study was to identify and assess, based on field observations, interviews and measurements, the risk to reproductive health from occupational health hazards (focusing on chemical hazards) that might be present in histopathology laboratories of the NHLS.It was expected that this study could sensitise, raise awareness and improve control strategies and procedures aimed at reducing reproductive health risks to both male and female workers in this particular work environment and in other NHLS laboratories. Materials and Methods This was a descriptive, cross-sectional study; the study population included five out of the fifteen existing NHLS histopathology laboratories in the country.Due to the limited time and resources available for this study four out of the five histopathology laboratories sampled were selected from the Gauteng Province (closest to the researcher) and an additional one from the Northern Cape Province. Results The reproductive health risk assessment process detailed in this report, has identified worker‟s exposure to formaldehyde during specimen cut-up, specimen storage and during the process of disposal and making up of formaldehyde solution, as potentially high risk. It also identified exposure to xylene vapours during the automated staining process (particularly when replacing chemicals in the equipment), as potentially high risk. Exposure to hazardous biological agents (HBAs) and various other chemical reagents, ergonomic stress and potential exposure to ionising radiation were identified as moderate reproductive health risks when performing specific histopathology laboratory processes. Discussion The outcome from the health risk assessment supported the conclusion from researchers reviewed in this study that reproductive health risks in the workplace warrant special consideration and exposure to specific hazards, such as organic solvents, might require the implementation of special measures to protect in particular, but not exclusively, pregnant workers. Some of the limitations related to this study include: limited research data on reproductive health and the difficulty of inferring from animal studies to human reproduction; another problem relates to the use of occupational exposure limits (OELs) as benchmark for acceptable or over-exposure, as OELs might be determined without sufficient consideration of reproductive health endpoints.Due to the limited scope of this study only the major chemical hazards identified (formaldehyde and organic solvents, including xylene) could be sampled. Recommendations Protection of laboratory workers from reproductive health hazards should follow the standard occupational hygiene hierarchy of control practice, i.e. substitution and engineering methods should get precedence over strategies that rely on personal protective equipment.Although the substitution of hazardous substances such as formaldehyde and xylene in pathology laboratories appears possible, the health and safety implications of using substitutes must be investigated carefully. Following observations made during this study it was recommended that local exhaust ventilation (LEV) systems should be maintained in good working order and their performance routinely tested, both by workers and by an external accredited body. Administrative measures which may include work restrictions and worker transfer should be implemented with caution, and always after thorough consultation with the individual worker. Such measures, when implemented, should be activated even before pregnancy is confirmed to prevent exposure during the crucial period of early foetal growth. It was recommended that the NHLS review the current policy and safe working procedure on pregnancy to include both male and female workers within reproductive age.In terms of personal protective equipment, it was recommended that when potential short-term, high exposure to formaldehyde or xylene is anticipated a half-mask respirator with the appropriate filtering media is applied. Workers must be adequately trained and fit tested to ensure that maximum protection is achieved.Additional information, more research data and detailed survey measurements will be required to substantiate the results of this assessment. In the meantime, the precautionary approach and best control practices should apply, to provide the maximum feasible protection for both males and female laboratory workers in their reproductive age.